Videografi: Kamera dan Teknik Pengambilan Gambar - D. Nunnun Bonafix (Bina Nusantara University, 2011)
Technology advances have greatly influenced in film and television development in the last decades. The purpose of this article is that videographers are able to increase their competence and skills in both mastering video camera and producing innovative and artistic work. A camera is one of the vital devices to take video pictures. In order to produce the best pictures, the camera mastery, the mastery of both the parts of the camera and the picture taking techniques, becomes an absolute point. Therefore, the abilities of the videographers can be improved significantly and they are able to produce the best and acknowledged work.